Intoxication, Provocation and Necessity as Defenses of Criminal Irresponsibility in the Judgments of Emperor Iyasu, and Emperor Dawit III of Ethiopia: A Historical Reflection - Chane, Gizachew Silesh; Mekonnen, Nega Ewunetie (Bahir Dar University Journal of Law, 2022)
Judgments rendered before the introduction of modern justice system in Ethiopia were largely subject to the final approval and analysis of the emperors. This trend continued to some extent until 1974; in this regard the Crown Court of Haile Selassie I was the first to be mentioned. Cases brought before the emperors’ courts were often criminal cases, and the judgments of the emperors reflected principles and concepts of criminal law that have been recognized in the criminal law of many countries today. This reflection presents three criminal cases brought before the courts of Emperor Iyasu, and Emperor Dawit III of Ethiopia and argues that the judgments of these two emperors are compatible with the principles of defenses of intoxication, provocation, necessity, and criminal responsibility.